A Valuable Research - Gasparyan, Gayane (Armenian Folia Anglistika, 2018)
Raphael Lemkin’s Draft Convention on Genocide and the 1948 UN Convention: A Comparative Discourse Study. S. Gasparyan, Sh. Paronyan, A. Chubaryan, G. Muradyan. Yerevan: YSU Press, 2016, 176 pp.